2021
DOI: 10.1177/20563051211052907
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Expression and User Predispositions: Applying the Differential Susceptibility to Media Effects Model to the Study of Issue Polarization

Abstract: The ability of social media users to express themselves online should be influential for opinion formation, including potential polarization. Still, little is known about how expression interacts with users’ psychological predispositions, especially for controversial topics. The potential for expression to relate to support for social media-based racial justice movements, which could also be affected by underlying feelings of racial resentment, is particularly interesting. We apply the Differential Susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The Differential Susceptibility to Media Effects Model (Valkenburg & Peter, 2013) posits that potential impact of and responses to media are contingent on individual differences. The themes of cultural socialization and processing discrimination may dovetail with other recent work in providing insight into the potential mechanisms relating digital media to individual differences (i.e., racial identity) in media impacts and responses (e.g., Coles & Saleem, 2021). Finally, these findings also contribute to literature exploring the potential affordances offered by digital media.…”
Section: Discussionmentioning
confidence: 86%
“…The Differential Susceptibility to Media Effects Model (Valkenburg & Peter, 2013) posits that potential impact of and responses to media are contingent on individual differences. The themes of cultural socialization and processing discrimination may dovetail with other recent work in providing insight into the potential mechanisms relating digital media to individual differences (i.e., racial identity) in media impacts and responses (e.g., Coles & Saleem, 2021). Finally, these findings also contribute to literature exploring the potential affordances offered by digital media.…”
Section: Discussionmentioning
confidence: 86%
“…Why it is so important for the social media natives of this study to not leave traces in “open” spaces online may be manifold, however (see, for example, Coles & Saleem, 2021; Laurison, 2015). One may start out by seeing their responses through the lens of their “distinct positionalities of privilege” (Fang et al, 2019, p. e11).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that people became further entrenched in their preconceived beliefs in the case of a contradicting opinion from a subject matter expert celebrity. In [131], the authors showed that feelings of resentment were the most significant predictor of the Black Lives Matter movement's support. Low-resentment individuals who expressed themselves on social media more frequently were less supportive.…”
Section: Polarization Dimension As Shown In Tablementioning
confidence: 99%